Multifocal pancreatic PPoma in the setting of MEN1: Case report and review of literature. (June 2021) - Mosenia, Arman; Ward, Casey; Yee, Alisa; Qorbani, Amir; Corvera, Carlos
Abstract: Introduction and importance: Functioning pancreatic neuroendocrine tumors (pNETs) that express pancreatic polypeptide—PPomas—do not yet have a pathognomonic clinical syndrome associated with them due to their overall rarity and diverse symptoms. Moreover, in patients with MEN1, the often multifocal nature of pNETs presents a unique clinical issue. Case presentation: We report a case of a 22-year-old man with a known MEN1 gene mutation who was suffering from severe diarrhea (7–8 bowel movements per day) and was found to have only elevated PP levels on biochemical work-up. Ga68-DOTATATE PET/CT showed multifocal tumors in the body and tail of the pancreas that were not evident on contrast-enhanced CT. The patient underwent a successful laparoscopic radical antegrade modular pancreatosplenectomy (RAMP) and recovered well post-operatively with complete resolution of his diarrhea. Immunohistochemistry showed multiple pure PPomas. Clinical discussion: This case highlights the unique propensity for multifocal disease in patients with MEN1 mutations and the utility of functional imaging by somatostatin analogs, i.e., Ga68-DOTATATE PET/CT, in order to perform oncologic laparoscopic pancreatic resections. Conclusion: PPomas in the setting of MEN1 mutations are a unique clinical entity due to their diverse associated clinical syndromes and propensity for multifocal disease. Highlights: PPomas have no pathognomonic clinical syndrome associated with them. Patients with MEN1 have a propensity for multifocal pNETs. DOTATE PET/CT is vital adjunct to pancreatic protocol CT for operative planning. Intra-operative ultrasound makes laparoscopic multi-focal pNET resection feasible. DOTATATE PET/CT surveillance is necessary due to high risk for recurrence in MEN1.